2005
DOI: 10.1007/s10809-005-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the States of Oxidation of Metals in Thin Oxide Films by X-Ray Photoelectron Spectroscopy

Abstract: Thin oxide films are widely used in microelectronics, heterogeneous catalysis, and nanotechnologies [1]. The requirements imposed on the manufacture and properties of these films are very high. One of the most important parameters responsible for the quality and physicochemical properties of oxide films is the oxidation state of metals in the films. Therefore, the qualitative and quantitative determination of the oxidation state of metals is an important analytical problem. It can be successfully solved using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…The W 4f spectrum confirms the presence of pure WO 3 which is clearly defined by the 4 f 7/2 peak set at 36.0 eV with doublet separation of 2.14 eV (Fig. 4d) [31]. Moreover the presence of oxygen O 1s peak corresponds to WO 3 both, in respect to binding energy À 531.0 eV [28].…”
Section: Xps Spectra Of W@wcwo 3 Support and Pd/w@wcwo 3 Catalystsupporting
confidence: 54%
“…The W 4f spectrum confirms the presence of pure WO 3 which is clearly defined by the 4 f 7/2 peak set at 36.0 eV with doublet separation of 2.14 eV (Fig. 4d) [31]. Moreover the presence of oxygen O 1s peak corresponds to WO 3 both, in respect to binding energy À 531.0 eV [28].…”
Section: Xps Spectra Of W@wcwo 3 Support and Pd/w@wcwo 3 Catalystsupporting
confidence: 54%
“…4952 We therefore decided to utilize this technique to further elucidate the oxidation state and effect of functionalization for these boron clusters. Boron XPS spectra for several representative clusters synthesized in our study (Figure 7) indicate a clear trend observed in the shift of B–B bond peak energies depending on the redox state of the functionalized cluster.…”
Section: Resultsmentioning
confidence: 99%
“…As the annealing temperature increases further to 350 °C, a decrease in 1T′‐phase doublets of both the W and Se core‐level spectra is observed. Figure e shows a growing broad peak at the binding energy of ≈30.76 eV, which indicates the partial decomposition of WSe 2 at high annealing temperatures resulting in the formation of metallic W . This corresponds with the rise in the broad peak at ≈53.25 eV after annealing at 350 °C (Figure f), which is attributed to the presence of elemental Se .…”
Section: Resultsmentioning
confidence: 79%